A method to study the role of DDX3 RNA helicase in HIV-1 - Chen, Chia-Yen (2010)
Viral replication requires the use of host cell proteins and enzymes. Many viruses utilize viral helicases at various stages of their life cycle; these viruses have evolved to encode directly helicase or helicase-like proteins. In contrast, the genomes of retroviruses are devoid of viral helicases. Human immunodeficiency virus (HIV-1) has adopted the ability to use one or more cellular RNA helicases for its replicative life cycle. In this chapter, we briefly summarize the approach for assaying the RNA unwinding activity of RNA helicasesd and measurement of the effect helicase inhibitors on HIV-1 replication.